A short report on the current landscape of Artificial Intelligence (AI) in vascular surgery in Pakistan - Nadeem Ahmed Siddiqui; Muhammad Anees; Fareed Shaikh; Zia Ur Rehman (Journal of the Pakistan Medical Association, 2024)
This study focuses on the current applications, potential, and challenges to Artificial Intelligence (AI) integration in vascular surgery with specific emphasis on its relevance in Pakistan. Despite the benefits of AI in vascular surgery, there is a substantial gap in its adoption in Pakistan compared to global standards. In our context with limited resources and a scarcity of vascular surgeons, AI can serve as a promising solution. It can enhance healthcare accessibility, improve diagnostic accuracy, and alleviate the workload on vascular surgeons. However, hurdles including the absence of a comprehensive vascular surgery database, a shortage of AI experts, and potential algorithmic biases pose significant challenges to AI implementation. Despite these obstacles, the study underscores the imperative for continued research, collaborative efforts, and investments to unlock the full potential of AI and elevate vascular healthcare standards in Pakistan. Continue...